Failed reciprocity in close social relationships and health: findings from the Whitehall II study - Chandola, Tarani (2007)
OBJECTIVE: To extend the model of effort-reward imbalance at work to close and more general social relationships and test the associations with different measures of health. Lack of reciprocity at work is associated with poorer health in a number of studies. However, few studies have analysed the effect of non-reciprocity in other kinds of social relationships on health. METHODS: The Whitehall II Study is an ongoing prospective study of British civil servants (N=10,308 at baseline in 1985–88). Cross-sectional data from the latest phase (7, N=6,944 in 2002–04) were used in the analyses. The main exposure was a questionnaire measuring non-reciprocal social relations in partnership, parent-children and general trusting relationships. Health measures included the SF-36 mental and physical component Scores, GHQ-30 depression subscale, Jenkins’ Sleep disturbance questionnaire and the Rose Angina questionnaire. Logistic and linear regression models were analysed, adjusted for potential confounders and mediators of the association. RESULTS: Lack of reciprocity is associated with all measures of poorer health. This association attenuates after adjustment for previous health and additional confounders and mediators, but remains significant in a majority of models. Negative social support from a close person is independently associated with reduced health, but adjusting for this effect does not eliminate the association of non-reciprocity with poor health. CONCLUSION: The effort-reward imbalance at work model has been extended to close and more general social relationships. Lack of reciprocity in partnership, parent-children and general trusting relationships is associated with poorer health.